“Low-For-Long” interest rates and banks’ interest margins and profitability: Cross-country evidence - Claessens, Stijn; Coleman, Nicholas; Donnelly, Michael (Journal of Financial Intermediation, 2018)
Interest rates in many advanced economies have been low for almost a decade now and are often expected to remain so. This creates challenges for banks. Using a sample of 3385 banks from 47 countries from 2005 to 2013, we find a one percentage point interest rate drop implies an 8 basis points lower net interest margin, with this effect greater (20 basis points) at low rates. Low rates also adversely affect bank profitability, but with more variation. And for each additional year of “low-for-long”, margins and profitability fall by another 9 and 6 basis points, respectively.